Systematic Review of the Implementation of Iron Supplementation for Adolescent Girls to Prevent Anemia in Urban and Rural Areas - Fitri, Fitri; Flora, Rostika; Idris, Haerawati (Jurnal KESANS : Kesehatan dan Sains, 2025)
Introduction: Anemia remains a public health problem in Indonesia, particularly among adolescent girls due to increased iron requirements during growth and menstruation. As an effort to prevent anemia, a national iron supplementation program is implemented in schools, but compliance remains low. Objective: To determine the implementation of iron supplementation in adolescents in urban and rural areas based on a review of the latest literature as an effort to prevent anemia. Methods : A literature review was conducted of publications from 2020–2025 obtained from national and international databases that met the inclusion criteria. Results and Discussion: Distribution coverage in Indonesia is >60%, but compliance ranges from 14–47%. Enabling factors include teacher support, ongoing education, and digital reminders, while barriers include tablet taste/odor, side effects, forgetfulness, and logistical constraints. International studies show that direct supervision can increase compliance to >80% and reduce the prevalence of anemia. Conclusion: Strengthening iron supplementation programs requires prioritizing strategies to increase adherence through school-based approaches, family engagement, digital innovation, and increased ease of consumption.